The roles of self-efficacy toward micro- entrepreneurs’ competency in Malaysia / Nuralina Mustamam - Mustamam, Nuralina (Faculty of Business and Management, 2020)
The purpose of this paper is to analyse the roles of self-efficacy toward micro- entrepreneurs’ competency in Malaysia. There are 4 different independent variables in this research which are marketing, innovation, management and risk-taking. The method used in this research was descriptive analysis or also known as correlational studies. A non-probability sampling was used in the experiment more specifically, judgment sampling. Researcher used Statistical Package for Social Science (SPSS) software to analyse data collected from 100 respondents. The analysis included analysis of descriptive, reliability and regression. The results from this project paper demonstrated a significant effect of management and risk-taking on micro- entrepreneurs’ competency, while the elements of marketing and innovation were trivial. Therefore, it is hoped this study will fill the gap of understanding the importance of self-efficacy in growing more competent micro-entrepreneurs.